2014
DOI: 10.1186/1471-230x-14-149
|View full text |Cite
|
Sign up to set email alerts
|

Health related quality of life in patients with chronic gastritis and peptic ulcer and factors with impact: a longitudinal study

Abstract: BackgroundThe assessment of Health Related Quality of Life (HRQOL) has been applied as a significant outcome indicator for patients with chronic diseases. No HRQOL study, however, has looked at HRQOL in patients with chronic gastritis and peptic ulcers. This paper focuses on comparing HRQOL in patients with chronic gastritis and peptic ulcers and examining the factors that influence the HRQOL of such patients. Results can be used for making decisions in clinical trials as well as aiding individual management a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 29 publications
0
25
2
2
Order By: Relevance
“…Studies conducted on adults with gastrointestinal diseases, such as peptic ulcers and gastroesophageal reflux, have reported lower life quality scores than the normal population, but also found significantly increased life quality scores after the treatment (26,27). A study on adults showed that patients with chronic gastritis had lower average scores when compared to those patients with peptic ulcers in all the life quality subscales, except for the physical functioning scale score (10). When compared with the normal population, both groups of patients had lower qualities of life scores (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted on adults with gastrointestinal diseases, such as peptic ulcers and gastroesophageal reflux, have reported lower life quality scores than the normal population, but also found significantly increased life quality scores after the treatment (26,27). A study on adults showed that patients with chronic gastritis had lower average scores when compared to those patients with peptic ulcers in all the life quality subscales, except for the physical functioning scale score (10). When compared with the normal population, both groups of patients had lower qualities of life scores (10).…”
Section: Discussionmentioning
confidence: 99%
“…Gastritis can affect an individual's daily activities, and this creates an important health problem from both the social and economic points of view. Gastritis may lead to an observable worsening in the quality of life (QoL) and affect the quality of sleep for adult patients (10,11). There are no studies in the contemporary international literature that are focused on the quality of sleep and life in children and adolescents with gastritis.…”
Section: Introductionmentioning
confidence: 99%
“…Wen et al (2014) also reported that patients with chronic gastritis had poor QOL compared to patients with peptic ulcers (except for PF domain), and both groups had lower QOL score compared to population norms (except for MH domain). After treatment, both groups experienced improved QOL after treatments (except for RP domain for both diseases) [27] . In a recent study by Kabakambira et al (2018) evaluated the impact of HR QOL using the Short Form Nepean Dyspepsia Index (SF-NDI) questionnnaire of PUD patients on standard antibiotic based triple therapy for 10 days, the improvement was much less in the metronidazole-based triple therapy than in the standard of care [28] .…”
Section: Assessment Of Qol Of Pud Patients On H Pylori Eradication Tmentioning
confidence: 96%
“…It is well known that alcohol abuse may cause acute erosive hemorrhagic gastritis, and long-term drinking could cause stomach disorders and chronic atrophic gastritis [5][6][7]. In general, gastritis is mainly due to the imbalance between aggressive and defensive factors of the gastric mucosa, which causes a variety of issues, from local defects to active inflammation [8][9][10][11]. This kind of chronic inflammation is increasingly recognized to have significant tumor-promoting potential [12,13].…”
Section: Introductionmentioning
confidence: 99%